2018
DOI: 10.18632/aging.101492
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine exposure impairs germ cell development in human fetal ovaries cultured in vitro

Abstract: In the present paper, we found that human fetal ovaries (at ~16 weeks) express the transcripts for several subunits of the nicotinic acetylcholine receptor (nAChR). Exposure to the drug in vitro resulted in the marked increase of apoptosis in the ovaries in a time and dose-dependent manner. Evidence that adverse nicotine effects are potentially due to an increased level of reactive oxygen species (ROS) and consequent DNA damage, both in the ovarian somatic cells and germ cells, are reported. After 4 days of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 66 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…The chosen nicotine concentrations were based on 12µg representing approximately 1% of the nicotine inhaled per cigarette (i.e. about 1.2mg per cigarette [32]) and 200µg representing approximately 1% of the nicotine inhaled by smoking 15-20 cigarettes per day [32]; these concentrations were also consistent with those used in previous studies [31,[33][34][35]. The treatments with CSE and nicotine had no significant effect on cell viability, as determined by flow cytometry (data not shown).…”
Section: Treatment Of Modcs With Cse or Nicotinesupporting
confidence: 62%
See 1 more Smart Citation
“…The chosen nicotine concentrations were based on 12µg representing approximately 1% of the nicotine inhaled per cigarette (i.e. about 1.2mg per cigarette [32]) and 200µg representing approximately 1% of the nicotine inhaled by smoking 15-20 cigarettes per day [32]; these concentrations were also consistent with those used in previous studies [31,[33][34][35]. The treatments with CSE and nicotine had no significant effect on cell viability, as determined by flow cytometry (data not shown).…”
Section: Treatment Of Modcs With Cse or Nicotinesupporting
confidence: 62%
“…This provides a molecular basis for the reported inhibition of DC maturation and function by CSE and nicotine [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The concentrations of CSE (0.5% and 3%) and nicotine (12µg/ml and 200µg/ml) employed in this study were based on those used in previous studies [24,27,28,30,31,[33][34][35]. Although the systemic blood concentrations of nicotine in smokers are much lower (20-60 ng/ml) [36,37], our aim was to produce a reasonable model of the concentrations of cigarette smoke constituents (including nicotine) in the tissues of the respiratory tract directly exposed to these tobacco constituents during smoking.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] Although the underlying relationship between smoking and earlier onset of menopause is not well defined, previous studies have hypothesized the irreversible toxic effect of smoking on ovarian function. 37,38 Nicotine has been found to induce apoptosis of ovarian culture that may reduce ovarian reserve oocytes. 37 Ruan and Mueck (2015) have demonstrated that smoking drastically affects both endogenous E2 and FSH levels and may cause a decrease or inactivation of the FSH hormone.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Nicotine has been found to induce apoptosis of ovarian culture that may reduce ovarian reserve oocytes. 37 Ruan and Mueck (2015) have demonstrated that smoking drastically affects both endogenous E2 and FSH levels and may cause a decrease or inactivation of the FSH hormone. 39 These observations agree with the E2 and FSH hormone profile among premature/early menopause in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Petrik et al found α2nAChR and α7nAChR expression in ovarian tissues and isolated granulosa cells and suggested that one mechanism by which nicotine may cause the folliculogenesis defects observed in adult female rats was through the induction of apoptosis in granulosa cells and/ or oocytes via activation of these receptors. 80,81 Harmych et al designated that nicotine inhibits MAPK signaling and spheroid invasion in ovarian cancer cells. 16 In this study, the results indicate that nicotine can suppress spheroid invasion and compaction as well as proliferation in ovarian cancer cell lines, and p38 and ERK MAPK signaling pathways are important mediators of these responses.…”
Section: Ovarian and Uterine Cancermentioning
confidence: 99%